Ultrasound assessment of renal blood flow as a method for early diagnosis of acute kidney injury in geriatric patients with peritonitis - Momot, N.; Vorotyntsev, S. I.; Воротинцев, Сергій Іванович (My University, 2021)
Aim of the study: to evaluate the predictive value of renal resistance index (RRI) and semiquantitative renal perfusion (SQP) as methods for early diagnosis of AKI in geriatric patients after urgent abdominal surgery.
Keywords: тези доповідей